The Impact of Peatland Fires on Cellulolytic Microbial Populations in Several Landuses - Novian Hendro; Zulfarina Zulfarina; Nurul Qomar (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Studies on the impact of peatland fires on agricultural land, especially oil palm, and rubber, are still limited. This study aims to calculate the total population of cellulolytic bacteria and determine the activity of cellulolytic enzymes qualitatively in each microbial isolate found and to determine the level of peatland degradation after the fire. The research was conducted by survey in the field. The research location is in the long jungle village of Tambang Subdistrict, Kampar Regency. At the same time, the laboratory analysis was carried out in the Pathology, Entomology, and Microbiology Laboratory, Faculty of Agriculture and Animal Husbandry, Sultan Syarif Kasim Riau University. Determination of sample points using the purposive sampling method, which is to choose a location per the study's objectives at 4 locations. The first location is oil palm land that is not burnt, the second is burning oil palm land, the third is unburned rubber land, and the fourth is burned rubber land. Each location was repeated three times to obtain 12 sample points for observation. Furthermore, at each observation sample point, two soil depths were observed, 0-15 cm and 15-30 cm. The total population of cellulolytic bacteria in oil palm and rubber plantations that were burned and not burned with different soil depths ranged from 5.3 x 109 cfu / g soil to 14.0 x 109 cfu / g soil. The clear zone ratio (Z / K) of 8 cellulolytic bacterial isolates observed was high criteria, namely> 1.76 (100%). The highest Z / K ratio was produced by bacterial isolates originating from burnt rubber plantations at a soil depth of 0-15 cm, namely 5.25.